2021
DOI: 10.3389/fped.2021.703695
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Evaluation of Pacifier Removal on Oro-Dentofacial Structures: A Controlled Clinical Trial

Abstract: It is well recognized that pacifier habit leads to occlusal and orofacial functional changes in children. However, the effects of the interruption of prolonged pacifier habit on the development of the dento-facial complex has not yet been fully characterized. Thus, the aim of this study was to investigate the influence of pacifier removal on aspects of oro-dentofacial morphology and function in preschool children. For that, a pacifier group (n = 28) and a control group (n = 32) of 4-year-old children with and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A study found that after removing the pacifier habit in 4-year-old children, the frequency of malocclusion and changes in breathing and speech decreased significantly. 15 Healthcare professionals who follow preschool-aged children should consider this natural correction while bearing in mind that early intervention in these habits is essential. Campos et al 26 did not find a statistically significant association between malocclusion and the mother's level of education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study found that after removing the pacifier habit in 4-year-old children, the frequency of malocclusion and changes in breathing and speech decreased significantly. 15 Healthcare professionals who follow preschool-aged children should consider this natural correction while bearing in mind that early intervention in these habits is essential. Campos et al 26 did not find a statistically significant association between malocclusion and the mother's level of education.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Studies on the prevalence of malocclusion in Portuguese children populations are scarce but have shown a considerable prevalence of these oral conditions in the primary dentition. 12,13 Since malocclusion can be related to some oral behaviors, namely non-nutritive sucking habits, 14,15 early diagnosis and intervention are essential for its control. Knowing the distribution and factors associated with malocclusion in the primary dentition will help understand the disease at those ages and plan and implement preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…Facial morphology was evaluated with a sliding caliper (Bone Caliper in aluminum 240 mm, Cescorf, Brazil) to determine the facial height (linear distance between the nasion and gnathion; n‐gn) and the bizygomatic width (distance between the zygomatic points; zy‐zy). The ratio between morphological facial height and bizygomatic distance was was also calculated (n‐gn/zy‐zy) (Scudine et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The morphological occlusion was evaluated from dental casts of the maxillary and mandibular arches and included (Baume, 1950; Foster & Hamilton, 1969): sagittal relationship of the primary molars (distal step, mesial step or flush terminal plane), incisors transversal and vertical relationship, maxillary and mandibular intercanine widths, maxillary and mandibular intermolar widths and palatal depth (Scudine et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation